2012
DOI: 10.1177/000494411205600203
|View full text |Cite
|
Sign up to set email alerts
|

‘I'm Telling You … The Language Barrier is the Most, the Biggest Challenge’: Barriers to Education among Karen Refugee Women in Australia

Abstract: This article examines factors influencing English language education, participation and achievement among Karen refugee women in Australia. Data were drawn from ethnographic observations and interviews with 67 participants between 2009 and 2011, collected as part of a larger qualitative study exploring the well-being of Karen refugee women in Sydney. Participants unanimously described difficulty with English language proficiency and communication as the ‘number one’ problem affecting their well-being. Gendered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 12 publications
1
110
0
Order By: Relevance
“…Louisa Benson Craig, a former Miss Burma, was one of the many Sgaw Karen women who held important military positions within the insurgency and later in the Karen Diaspora community in the U.S. Today, Karen women, such as the award-winning author, Zoya Phan (see Phan, 2010), are important spokespeople in the Karen Diaspora community. However, like Watkins, Razee, and Richters' (2012) study of Karen women in Australia, I found some troubling trends related to Karen women and girls in the U.S.…”
Section: Gendermentioning
confidence: 74%
“…Louisa Benson Craig, a former Miss Burma, was one of the many Sgaw Karen women who held important military positions within the insurgency and later in the Karen Diaspora community in the U.S. Today, Karen women, such as the award-winning author, Zoya Phan (see Phan, 2010), are important spokespeople in the Karen Diaspora community. However, like Watkins, Razee, and Richters' (2012) study of Karen women in Australia, I found some troubling trends related to Karen women and girls in the U.S.…”
Section: Gendermentioning
confidence: 74%
“…Forty seven nominated English language as their single biggest challenge, and their accounts of their experiences varied across the three samples with different educational settings. Many researchers and advocates emphasise the impact of language barriers on refugees' settlement experiences (e.g., VEOHRC 2008; Watkins et al 2012;Deng & Marlowe 2013;Stroud & Ibrahim 2016). In the present study, English language was not merely a difficulty facing refugees; it was substantially bigger than ten other challenges, and endorsed as such by a diverse group of refugees varying in educational setting, cultural background, and time lived in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Their accounts of their schoolwork experiences suggest that young refugees would benefit as much from support with academic English as they do from support learning conversational English. As advocates have noted, such support would likely require much more time than the allocated 510 hours (Matthews 2008;Watkins et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has been found that trainers cannot assume that all participants in training courses understand the technical terminology used (Welsh, 2012). Furthermore, international students often explain difficulty with English language expertise and communication as the main difficulty affecting their wellbeing (Watkins, Razze, & Richters, 2012). Thus, language barriers are possibly some of the most common problems for international students from diverse linguistic backgrounds.…”
Section: Second Language Learningmentioning
confidence: 99%